Strategi Adaptasi Pengemudi Becak Motor Terhadap Keberadaan Transportasi Motor Online di Kota Pekanbaru (Studi Pangkalan Becak Simpang Kualu) - Farin Fitri Syahdila; Teguh Widodo (Peneliti.net, 2023)
Motorized rickshaws are a modern means of transportation from bicycle rickshaws to modified motorized rickshaws and are still around today. This study discusses the adaptation strategy of motorized pedicab drivers to the existence of online motorized transportation in the city of Pekanbaru (study of the Kualu Simpang Becak Base). The purpose of the strategy research was carried out by motorized trishaw drivers and the reasons why pedicab drivers still exist and have survived to this day. This study used a descriptive qualitative method using a purposive sampling technique. In this study, there were 7 informants out of 20 existing drivers based on existing criteria. The research is located in Jln Suka Karya, Tuah Karya Village, Tuah Madani District. For data instruments using observation, interviews, and documentation. The results of the study show that motorized rickshaw drivers use 3 strategies to do their job. There are active, passive, and network strategies, and the results of the second discussion show that motorized rickshaw drivers survive because income, social, and work are gone, so they still survive today.